RNA-binding FMRP and Staufen sequentially regulate the Coracle scaffold to control synaptic glutamate receptor and bouton development. - Song, C.; Leahy, S.N.; Rushton, E.M.; Broadie, K. (Development, 2022)
Both mRNA-binding Fragile X mental retardation protein (FMRP; Fmr1) and mRNA-binding Staufen regulate synaptic bouton formation and glutamate receptor (GluR) levels at the Drosophila neuromuscular junction (NMJ) glutamatergic synapse. Here, we tested whether these RNA-binding proteins act jointly in a common mechanism. We found that both dfmr1 and staufen mutants, and trans-heterozygous double mutants, displayed increased synaptic bouton formation and GluRIIA accumulation. With cell-targeted RNA interference, we showed a downstream Staufen role within postsynaptic muscle. With immunoprecipitation, we showed that FMRP binds staufen mRNA to stabilize postsynaptic transcripts. Staufen is known to target actin-binding, GluRIIA anchor Coracle, and we confirmed that Staufen binds to coracle mRNA. We found that FMRP and Staufen act sequentially to co-regulate postsynaptic Coracle expression, and showed that Coracle, in turn, controls GluRIIA levels and synaptic bouton development. Consistently, we found that dfmr1, staufen and coracle mutants elevate neurotransmission strength. We also identified that FMRP, Staufen and Coracle all suppress pMad activation, providing a trans-synaptic signaling linkage between postsynaptic GluRIIA levels and presynaptic bouton development. This work supports an FMRP-Staufen-Coracle-GluRIIA-pMad pathway regulating structural and functional synapse development.